Identifying the Challenges that Hinder Research Productivity in Academia: Evidence from Somaliland and The Way Forward. - Jama, Khalid (AUC Knowledge Fountain, 2024)
In any nation, research is the primary force behind innovation and progress. It contributes to the Economic growth, global competence, and social progress. Research productivity is highly valued in the scientific community. Scientific community research is regarded as the key factor determining academic recognition, financial support, and academic recognition. Nonetheless, the output of research faces difficulties in many sub-Saharan African nations. This study aims to understand what limits the research publication in Somaliland. The study adopt a mixed methods approach to understand and analyze the main reason behind the research and publication limitations in Somaliland’s higher education. Individuals from various research and university settings who have experienced a wide range of working conditions and academic accomplishments are interviewed and surveyed. The findings reveal that precarity, lack of funding, limited number of Ph.D. holders, difficulty of data and literature accessibility, and obstacles in technology are the main reasons that contribute to the limitation of the country’s research output. In the findings, there is a clear alignment between quantitative and qualitative data. Increasing the number of Ph.D. holders, developing contractual agreements that reduce precarity, and prioritizing funding mechanisms are some of the recommended interventions of this study.